Dietary nano-selenium relieves hypoxia stress and, improves immunity and disease resistance in the Chinese mitten crab (Eriocheir sinensis). (July 2016) - Qin, Fenju; Shi, Miaomiao; Yuan, Hongxia; Yuan, Linxi; Lu, Wenhao; Zhang, Jie; Tong, Jian; Song, Xuehong
Abstract: Hypoxia is a relevant physiological challenge for crab culture, and the hemolymph plays a crucial role in response to the hypoxia. In a 60 d feeding trial, Chinese mitten crabs ( Eriocheir sinensis ) fed a diet containing 0.2 mg/kg nano-selenium (nanoSe) showed a significantly increased weight gain rate (WGR) and a reduced feed coefficient (FC) compared to those fed diets with 0, 0.1, 0.4, 0.8, and 1.6 mg/kg nanoSe. Another 90 d feeding trial was conducted to determine the influence of dietary nanoSe on the immune response in juvenile Chinese mitten crabs kept under the condition of hypoxia. The results showed that hypoxia stress resulted in significantly increased hemocyte counts (THC, LGC, SGC, and HC), expression levels of the hemocyanin gene and protein, lactic acid level, and antioxidant capacity (T-AOC activities, SOD activities, GSH-Px and GSH content) in hemolymph supernatant. When these crabs were infected with Aeromonas hydrophila bacteria, hypoxia exposure increased mortality, but it was alleviated by a diet supplemented with 0.2 mg/kg nanoSe. The up-regulative effects of nanoSe (0.2 mg/kg) on antioxidant capacity, hemocyte counts, and hemocyanin expression under hypoxia exposure were further strengthened throughout, whereas lactic acid levels induced by hypoxia stress were restored. Thus, the observations in this study indicate that the level of dietary nanoSe is important in regulating immunity and disease resistance in crabs kept under hypoxia stress. Highlights: Hypoxia down-regulated the immunity of crabs to Aeromonas hydrophila bacteria. Hypoxia stress increased hemocytes counts and antioxidant capacity during short time. Hypoxia stress increased mRNA/protein expression of hemocyanin during short time. NanoSe alleviated the down-regulative effects of the crabs'immunity induced by hypoxia. NanoSe extended the up-regulative effects of hemocytes counts, antioxidant capacity and hemocyanin expression.